Morphology of the last instar larva and pupa of Paranthrene diaphana (Dalla Torre & Strand 1925) (Lepidoptera: Sesiidae), a serious pest of the babylon weeping willow trees in Iran - Bąkowski, Marek; Askarianzadeh, Alireza (Zootaxa, 2023)
This work presents the first description of the morphology of the last larval instar and pupa of the clearwing moth species Paranthrene diaphana (Dalla Torre & Strand, 1925). All diagnostic morphological features are described in detail, compared with the closely related species Paranthrene tabaniformis (Rottemburg, 1775) and P. insolitus Le Cerf 1914, and the features are illustrated with photographs and line drawings. The research on clearwing moths in Tehran Province (central Iran) has revealed that P. diaphana is a serious new pest that causes significant damage to babylon weeping willow trees Salix babylonica L. (Salicaceae).